Comparative yield risk calculations of sour cherry and pear varieties regarding risk aversion - Persely, Szilvia; Ertsey, Imre; Ladányi, Márta (Applied Studies in Agribusiness and Commerce, 2012)
Fruit production in the world is increasing continuously. Though in the past few years China and some South-American countries have extended their fruit producing areas, Europe remains to be one of the greatest fruit producers in the world. In the middle of Europe Hungary has to face several challenges as competing for market. Since yield risk has an important role in Hungarian fruit production we investigate the yield risk of two of the most important sour cherry varieties (’Újfehértói fürtös’ and ’Oblacsinszka’) grown in Újfehértó (1984-2005), moreover, two of the most important pear varieties (’Bosc Beurre’ and ’Williams’) grown in Bánfa and Zalasárszeg (1984-2009). In the examined periods we analyse yield risk with different comparative methods such as E,V-efficiency, first and second degree as well as generalized stochastic dominance methods. We conclude that the production of sour cherry variety ’Oblacsinszka’ in Újfehértó is more preferable compared to the other sour cherry varieties and pear variety ’Bosc Beurre’ in Bánfa is more advantageous than the other pear varieties and sites.